THE LANDSCAPE MEMORY: THE SPECTACULAR, THE AUDIBLE, AND THE BODY - Priyatna, Endang Suryana (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2016)
This essay begins with a simple observation on a popular drawing theme: landscape drawing. The image of the landscape appears to be unchanging nevertheless the landscape itself was rapidly transformed as a result of Indonesian developmental and modernisationprogrammes. The essay attempts to argue that the image is a form of cultural memory: a memory about the nature, the mother nature, and the motherland. Under the New Order regime, the link between the image and the memory was (re)used for disciplinary action to maintain order and stability. This was articulated in the form of cultural practices. In this essay, SenamKesegaranJasmani (Massphysical exercises) and UpacaraBendera (Flag ceremony) are the cultural practices under discussion. Both practices are analysed as disciplinary action towards the body by means of internalisation, memorisation, and reproduction of the landscape through physical movement and auditioning (power of hearing and listening). The essay offers a non conclusive conclusion that these practices are linked to the formation of collective memory of being a nation.